2020
DOI: 10.1186/s12933-020-01083-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) predicts recurrent worse outcomes in type 2 diabetes mellitus patients with prior cardiovascular events: a prospective, observational cohort study

Abstract: Background: Merging studies have reported the association of lipoprotein(a) [Lp(a)] with poor outcomes of coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM). However, the prognostic importance of Lp(a) for recurrent cardiovascular events (CVEs) is currently undetermined in patients with T2DM and prior CVEs. Methods: From April 2011 to March 2017, we consecutively recruited 2284 T2DM patients with prior CVEs. Patients were categorized into low, medium, and high groups by Lp(a) levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…The results showed that when CVD was combined with T2DM, the cardiovascular risks associated with Lp(a) might further increase. 35 There are also occasional reports indicating that increased Lp(a) levels are associated with arterial calcification and venous thrombotic disease, but more evidence is needed to confirm this finding.…”
Section: Correlation Between Lp(a) Levels and Cvdmentioning
confidence: 99%
“…The results showed that when CVD was combined with T2DM, the cardiovascular risks associated with Lp(a) might further increase. 35 There are also occasional reports indicating that increased Lp(a) levels are associated with arterial calcification and venous thrombotic disease, but more evidence is needed to confirm this finding.…”
Section: Correlation Between Lp(a) Levels and Cvdmentioning
confidence: 99%
“…Noteworthy, Lp (a) is known to have atherothrombogenic property by inhibiting fibrinolysis system and promoting thrombus formation. In spite of a very skewed distribution, elevated circulating Lp(a) has emerged as an independent predictor of adverse outcomes for both general and higher risk populations, especially when LDL-C levels are elevated ( 32 ). In observational studies of patients with stable CAD, serum Lp(a) levels decreased stepwise across angiographic coronary collateral grade, and elevated Lp(a) predicted poor collateral development ( 33 , 34 ).…”
Section: Impact Of Diabetic Dyslipidemia On Collateral Formationmentioning
confidence: 99%
“…Several large-scale cohort studies have shown an inverse association between T2DM risk and Lp(a) levels, which has not been validated through Mendelian randomization trials [ 11 13 ]. A limited number of studies have explored this association in Asian populations, with inconsistent results [ 14 , 15 ]. Therefore, this study aimed at exploring the association between Lp(a) concentrations and T2DM, and to evaluate potential modification factors in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%